Application of high-throughput sequencing in understanding human oral microbiome related with health and disease - Chen, Hui; Jiang, Wen (Frontiers in Microbiology, 2014)
The oral microbiome is one of most diversity habitat in the human body and they are closely related with oral health and disease. As the technique developing,, high throughput sequencing has become a popular approach applied for oral microbial analysis. Oral bacterial profiles have been studied to explore the relationship between microbial diversity and oral diseases such as caries and periodontal disease. This review describes the application of high-throughput sequencing for characterization of oral microbiota and analyzing the changes of the microbiome in the states of health or disease. Deep understanding the knowledge of microbiota will pave the way for more effective prevent dentistry and contribute to the development of personalized dental medicine.